Odpowiedzi

Najlepsza Odpowiedź!
2009-11-19T20:14:08+01:00
A) n²(n-1)(n²+1) = n²(n³+n -n² -1 ) =n⁵ + n³-n⁴-n²
b) n²(n+1)(n²-1) = n²(n³-n +n² -1 ) =n⁵ - n³+n⁴-n²
c) (a-b)(a²+ab+b²)= a³ + a²b +ab² -a²b -ab² -b³ =a³ -b³
d) (x²+x+1)(x²-x+1) =x⁴-x³+x² +x³- x² +x +x²-x+1 =x⁴+x² +1
45 4 45
2009-11-19T20:21:12+01:00
A)n²(n-1)(n²+1)=(n³+n²)(n²+1)=n5+n³+n4+n² 5 i 4 to potęgi
b)n²(n+1)(n²-1)=to samo
c)(a-b)(a²+ab+b²)=a³+a²b+ab²+a²b+ab²+b³=a³+2a²b+2ab²+b³
d) (x²+x+1)(x²-x+1) = x4-x³+x²+x³-x²+x+x²+x+1=x4+x+x²+1
;p
14 3 14
2009-11-20T00:32:38+01:00
N²(n-1)(n²+1) = n²(n³+n -n² -1 ) =n⁵ + n³-n⁴-n²
n²(n+1)(n²-1) = n²(n³-n +n² -1 ) =n⁵ - n³+n⁴-n² (a-b)(a²+ab+b²)= a³ + a²b +ab² -a²b -ab² -b³ =a³ -b³
(x²+x+1)(x²-x+1) =x⁴-x³+x² +x³- x² +x +x²-x+1 =x⁴+x² +1
5 4 5